2018
DOI: 10.1590/s0100-204x2018000300009
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization of high-yield corn with poultry litter based on nitrogen doses

Abstract: The objective of this work was to recommend nitrogen doses from poultry litter-based organic fertilizers in powder and pellet forms, compared with mineral fertilizer, in a high-yield corn crop under no-tillage. The treatments consisted of a 3×3+1 factorial arrangement, with: three fertilizers, two organic derived from poultry litter in powder (OPo) and pelletized (OPe) forms and one mineral fertilizer (M); three N doses of 65, 100, and 135% of the recommended N requirement for corn; and an unfertilized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…6 Therefore, reasonable and precise fertilizer application is essential for growth and development of maize as well as for the protection of the ecological environment. 7 − 9 At present, the main fertilizer application methods for maize in China are one-time application with seeding fertilizer, 10 deep soil stratified fertilizer application, 11 or full-layer fertilizer application. 12 The one-time application method has low fertilizer utilization efficiency and is prone to environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Therefore, reasonable and precise fertilizer application is essential for growth and development of maize as well as for the protection of the ecological environment. 7 − 9 At present, the main fertilizer application methods for maize in China are one-time application with seeding fertilizer, 10 deep soil stratified fertilizer application, 11 or full-layer fertilizer application. 12 The one-time application method has low fertilizer utilization efficiency and is prone to environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Maize is widely planted, has a long reproductive cycle and high yield, and requires more fertilizer than other cereal crops, As shown in the literature, fertilizer applied, according to the local normal urea fertilization amount, is 6.5 kg of urea per mu for soybean and 26 kg per mu for corn, and the rest are treated according to conventional field management, without additional fertilizer application . Therefore, reasonable and precise fertilizer application is essential for growth and development of maize as well as for the protection of the ecological environment. At present, the main fertilizer application methods for maize in China are one-time application with seeding fertilizer, deep soil stratified fertilizer application, or full-layer fertilizer application . The one-time application method has low fertilizer utilization efficiency and is prone to environmental pollution. , The stratified application method applies a certain amount of fertilizer into the soil at a certain depth in layers at one time; this method can meet the needs of maize growth cycle, and it can improve the efficiency and reduce pollution to the environment. , Studies on stratified fertilizer application of maize in the literature showed that the yield of maize has a significant advantage over the quantity of fertilizer applied in one shallow or one deep application and can replace the traditional phased application in some areas.…”
Section: Introductionmentioning
confidence: 99%
“…The use of poultry litter increased the N and C contents in soils ( Figures 1A, 1B, 1C and 1D), since poultry litter is considered N source. Poultry litter supplied N requirements in maize increasing crop yields (Corrêa et al, 2018). Interestingly, all wastes were amended to supply about the same amount of N. The fact that poultry litter sustained higher N levels in both locations indicated that a more stable form of the nutrient occurs in this organic substrate (Pitta et al, 2012;Corrêa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Poultry litter supplied N requirements in maize increasing crop yields (Corrêa et al, 2018). Interestingly, all wastes were amended to supply about the same amount of N. The fact that poultry litter sustained higher N levels in both locations indicated that a more stable form of the nutrient occurs in this organic substrate (Pitta et al, 2012;Corrêa et al, 2018). Besides supplying N to plants, the role of poultry litter on Stenocarpella inoculum was not clear and may have even been detrimental, increasing pathogen inoculum.…”
Section: Discussionmentioning
confidence: 99%
“…Soil organic matter (SOM) participates in various biological, chemical, and physical soil processes that determine the productive potential of the soil (Mafra et al, 2014). Organic carbon (OC) is the main constituent of SOM which is influenced by the soil class characteristics and soil management system (McCarthy et al, 2008), including the fertilization practice, with both inorganic and organic fertilizers (Corrêa et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%